Does childhood adversity account for poorer mental and physical health in second-generation Irish people living in Britain? Birth cohort study from Britain (NCDS). Issue 3 (1st March 2013) - Das-Munshi, Jayati; Clark, Charlotte; Dewey, Michael E; Leavey, Gerard; Stansfeld, Stephen A; Prince, Martin J
Abstract : Objectives: Worldwide, the Irish diaspora experience elevated mortality and morbidity across generations, not accounted for through socioeconomic position. The main objective of the present study was to assess if childhood disadvantage accounts for poorer mental and physical health in adulthood, in second-generation Irish people. Design: Analysis of prospectively collected birth cohort data, with participants followed to midlife. Setting: England, Scotland and Wales. Participants: Approximately 17 000 babies born in a single week in 1958. Six per cent of the cohort were of second-generation Irish descent. Outcomes: Primary outcomes were common mental disorders assessed at age 44/45 and self-rated health at age 42. Secondary outcomes were those assessed at ages 23 and 33. Results: Relative to the rest of the cohort, second-generation Irish children grew up in marked material and social disadvantage, which tracked into early adulthood. By midlife, parity was reached between second-generation Irish cohort members and the rest of the sample on most disadvantage indicators. At age 23, Irish cohort members were more likely to screen positive for common mental disorders (OR 1.44; 95% CI 1.06 to 1.94). This had reduced slightly by midlife (OR 1.27; 95% CI 0.96 to 1.69). Although at age 23 second-generation cohort members were just as likely to report poorer self-rated health (OR 1.06; 95% CI 0.79 to 1.43), by midlife this difference had increased (OR 1.25; 95% CI 0.98 to 1.60). Adjustment for childhood and early adulthood adversity fully attenuated differences in adult health disadvantages. Conclusions: Social and material disadvantage experienced in childhood continues to have long-range adverse effects on physical and mental health at midlife, in second-generation Irish cohort members. This suggests important mechanisms over the life-course, which may have important policy implications in the settlement of migrant families.